Serum HDL cholestrol and glycemic status assessment in post-menopausal women - Ranabhat, Pashupati; Yadav, Shekhar (Journal of Chitwan Medical College, 2017)
Menopause is the consequence of the exhaustion of ovarian follicles which results in decreased production of estradiol and other hormones. Menopause is associated with a significant increase in cardiovascular diseases (CVD). Postmenopausal women have higher blood sugar values as compared to the control group because the estrogen hormone which makes the body cells more receptive or sensitive to insulin is either not secreted at all or is in limited supply. The estrogen hormone in females is protective for developing diabetes. Estrogen seems to contribute to glucose homeostasis in women. Significant negative correlation between fasting blood sugar and HDL with (r=-0.130, p= 0.369), suggesting that the fasting blood glucose levels were elevated whereas HDL levels were low normal in postmenopausal women thus associate with high risk of CVD in postmenopausal women.